Main methods of treatment of produced water in offshore oil production units - Viana Junior, Antonio Marcos; Altoé, Leandra; Agostinho da Silva Baila Madeira Antunes, Pedro; Martins Pereira Júnior, Antonio Augusto (Latin American Journal of Energy Research, 2023)
In the oil and gas extraction process, a by-product called “produced water” is generated, which contains pollutants and needs to be treated before being discarded in the environment. The objective of this work was to analyze the main methods of treatment of water produced in offshore oil production units. These treatments are divided into primary, secondary, and tertiary. Among the primary methods, the following stand out: hydrocyclone; API separator; and coagulation, flocculation and sedimentation. With regard to secondary methods, it is worth mentioning: flotation; and filtration and adsorption. And as for tertiary methods, it is emphasized: advanced oxidation processes; and membranes. As disposal at sea is the most common destination for produced water, it is important to use an appropriate combination of treatments to mitigate the environmental impacts of this activity.